1966
DOI: 10.1007/bf00203972
|View full text |Cite
|
Sign up to set email alerts
|

The isotopic constitution of sulphur in some stratiform lead-zinc sulphide ores

Abstract: Sulphur isotope measurements on five Australian stratiform lead-zinc sulphide ores are presented. Each deposit is characterised by a conspicuously narrow spread of values, mean g a~S heavier than meteoritic, average crustal, and, where sampled stratigraphically, 884S related to stratigraphy rather than propinquity. When considered with other deposits of the same class from elsewhere, several seemingly general features appear: Mean 8 a~S heavier than meteoritics; ranges for individual deposits narrow and rarely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

1969
1969
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…), c534S values for all ore sulphides range from -2.9%0 to 8.8%o (incorporating the values of Stanton and Rafter (1966)), with a mode at 4.5%0, and a mean of 3.6%0 (Fig. 6).…”
Section: Dugald River Pb-zn Prospectmentioning
confidence: 96%
See 3 more Smart Citations
“…), c534S values for all ore sulphides range from -2.9%0 to 8.8%o (incorporating the values of Stanton and Rafter (1966)), with a mode at 4.5%0, and a mean of 3.6%0 (Fig. 6).…”
Section: Dugald River Pb-zn Prospectmentioning
confidence: 96%
“…Sulphur isotopic data presented as histograms for Eastern Succesion epigenetic Cu + Au prospects Hampden, Mt Cobalt, Answer, Swan/Mt Elliot, Magnet and Mt Roseby. Data is also presented for the shale-hosted Dugald River ores (including seven samples from Stanton and Rafter (1966)), and for the Pegmont BIF-hosted Pb-Zn mineralisation (data from Vaughan and Stanton (1986)) l0 Nisbet et al (1983) identified Mount Cobalt as a shearcontrolled lode on the faulted contact between a metadolerite sill and metasediments of the Kuridala Fm. The main primary ore mineral in veins and shears is cobaltite (sampled in this study), with minor chalcopyrite, galena, pyrite, sphalerite and scheelite.…”
Section: "mentioning
confidence: 99%
See 2 more Smart Citations
“…Fijando de manera unívoca todos los parámetros de los que depende, se puede realizar un seguimiento de esta variable en función del tiempo. El principal parámetro es la temperatura (Urey, 1947), aunque también caben destacar la presión (Garlick el al., 1971;Clayton el al., 1975), la composición química (O'Neil, 1986;Taylor y O'Neil, 1977;Staton y Rafter, 1966;Sakai, 1968;Caballero, 1989), la estructura cristalina y morfología (Romanek el al., 1992;Rubinson y Clayton, 1969). El control de la fase polimórfica del precipitado resultante es uno de los parámetros más difíciles de fijar (Romanek el al., 1992).…”
Section: Introductionunclassified